Inherited genetic late‐onset erythropoietic protoporphyria: A systematic review of the literature. Issue 5 (21st February 2021) - Noyman, Yehonatan; Edel, Yonatan; Snast, Igor; Sherman, Shany; Kaftory, Ran; Lapidoth, Moshe; Mimouni, Daniel; Hodak, Emmilia; Levi, Assi
Abstract: Background: Inherited genetic erythropoietic protoporphyria (EPP) is characterized by a photosensitive rash that emerges during infancy or early childhood. Acquired EPP can erupt at any age, even during adulthood, and is associated with hematological disorders. A third, less‐studied type of EPP is also inherited but appears later in life (during adulthood). Purpose: To evaluate the characteristics of inherited genetic late‐onset (IGLO) EPP. Methods: A systematic comprehensive search of the literature was conducted using PubMed, Google Scholar, ScienceDirect, and clinicaltrials.gov databases. Studies describing patients with IGLO EPP were included. Additionally, we present an index case of a patient, treated at our clinic in whom inherited genetic EPP was diagnosed at age 21 years. Results: The search yielded 1514 citations. Five publications were eligible for review. Along with our case, 7 patients (4 males) were included in the analysis. Mean age at disease onset was 34.2 years (range 18‐69, median 30). Most patients presented with mild pruritus and rash in a photosensitive distribution. Mean level of free erythrocyte protoporphyrin IX (FEP) was 8.6 μmol/L. A mutant ferrochelatase gene ( FECH ) in trans to a hypomorphic FECH allele was found in 3 of the 4 patients who underwent genetic testing. Conclusion: We describe the distinct features of IGLO EPP. This work emphasizes that a diagnosis of inherited genetic EPP should not be ruled out in adults with new‐onset photosensitive manifestations.